1985
DOI: 10.1126/science.3898365
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the GDP Domain of EF-Tu and Location of the Amino Acids Homologous to ras Oncogene Proteins

Abstract: A 2.7 angstrom resolution x-ray diffraction analysis of a trypsin-modified form of the Escherichia coli elongation factor Tu reveals that the GDP-binding domain has a structure similar to that of other nucleotide-binding proteins. The GDP ligand is located at the COOH-terminal end of the beta sheet and is linked to the protein via a Mg2+ ion salt bridge. The location of the guanine ring is unusual; the purine ring is located on the outer edge of the domain, not deep within a hydrophobic pocket. The amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
313
1
3

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(333 citation statements)
references
References 16 publications
16
313
1
3
Order By: Relevance
“…Th~s conclusson ~s also supported by the further observation that the blndlng of GTP~S, Fluorescence enhancement of the EF-Tu tryptophan has been observed m the cases of EF-Tu denaturation in 6 M guamne HCI (Hazlett and Jameson, unpubhshed) or SDS [19] and for the GTP-form of the protein [19]. Information from the crystal structure [20,21] and sequence data [22] have assigned the single tryptophan to res)due 184 withln the GDP-binding domam and near the nucleottde site Fluorescence quenching data have described the tryptophan environment as relatively in. accessible to the solvent [23] suggesting an interior fac.…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Th~s conclusson ~s also supported by the further observation that the blndlng of GTP~S, Fluorescence enhancement of the EF-Tu tryptophan has been observed m the cases of EF-Tu denaturation in 6 M guamne HCI (Hazlett and Jameson, unpubhshed) or SDS [19] and for the GTP-form of the protein [19]. Information from the crystal structure [20,21] and sequence data [22] have assigned the single tryptophan to res)due 184 withln the GDP-binding domam and near the nucleottde site Fluorescence quenching data have described the tryptophan environment as relatively in. accessible to the solvent [23] suggesting an interior fac.…”
Section: Methodsmentioning
confidence: 82%
“…The exact nature of the resulting conformational change ~s not presently known for any of the G proteins under study. Of the GTP-blnding proteins being mvestlgated, EF-Tu is probably the best understood w~th data on the crystal structure for the GDP form having been reported [20,21]. Other G proteins, with the exceptlon of the ras p21 proteins [15-I'7], have yet to be crystalhzed and little ~s known about their overall structure.…”
Section: Methodsmentioning
confidence: 99%
“…During the course of trypsinolysis, the N-terminal pot- GTP/GDP binding site of IF2, in the middle of the structural elements conserved among G-proteins [14,15] but no binding of fMet-tRNA with this part of the molecule has ever been observed and under no circumstance has it been found that the binding of GTP or GDP and fMet-tRNA to IF2 may influence each other [6,16]. Thus, it is unlikely that the protection of this site by the initiator tRNA might be due to a direct interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Ha-ras p21, with known three-dimensional structure [1][2][3][4] and one of the best characterized members of this class of proteins [5][6][7][8]. It has been the object of intensive mutagenesis by diverse procedures (for references, see [9]).…”
Section: Introduction Ef-tu Is the Only Gtp Binding Protein Togethermentioning
confidence: 99%